2016
DOI: 10.1371/journal.pone.0168260
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Basal Signaling Regulation, Oligomerization, and Structural Organization of the Human G-Protein Coupled Receptor 83

Abstract: The murine G-protein coupled receptor 83 (mGPR83) is expressed in the hypothalamus and was previously suggested to be involved in the regulation of metabolism. The neuropeptide PEN has been recently identified as a potent GPR83 ligand. Moreover, GPR83 constitutes functionally relevant hetero-oligomers with other G-protein coupled receptors (GPCR) such as the ghrelin receptor (GHSR) or GPR171. Previous deletion studies also revealed that the long N-terminal extracellular receptor domain (eNDo) of mGPR83 may act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…The identification of an additional candidate peptide ligand for GPR83 should further facilitate characterization of GPR83 biology. GPR83 has been reported to be activated by multiple modalities, including basal activity regulated by the N-terminal extracellular domain, 21,22 Zinc(II), 19 and most prominently the ligand neuroendocrine peptide PEN. 20 PEN is a peptide hormone with no significant homology to FAM237A (2% identity of mature forms by Clustal Omega 11 ) that is derived from the precursor proSAAS encoded by the PCSK1N gene, which is processed into at least five other peptides: SAAS, GAV, PEN, bigLEN, and littleLEN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of an additional candidate peptide ligand for GPR83 should further facilitate characterization of GPR83 biology. GPR83 has been reported to be activated by multiple modalities, including basal activity regulated by the N-terminal extracellular domain, 21,22 Zinc(II), 19 and most prominently the ligand neuroendocrine peptide PEN. 20 PEN is a peptide hormone with no significant homology to FAM237A (2% identity of mature forms by Clustal Omega 11 ) that is derived from the precursor proSAAS encoded by the PCSK1N gene, which is processed into at least five other peptides: SAAS, GAV, PEN, bigLEN, and littleLEN.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further confirmatory studies that FAM237A (and FAM237B) is a physiologically relevant GPR83 ligand must also be done, including generation of GPR83 binding curves, specific activity in cells endogenously expressing GPR83, and characterization of the mature peptide form in a cell that endogenously expresses FAM237A. GPR83 has been reported to form hetero-oligomers with other GPCRs, including GPR171, 20 GHSR, MC3R, and MC4R; 21 thus, the ability of FAM237A and FAM237B to activate GPR83 hetero-oligomers should also be assessed. The E. coli -produced FAM237B had significantly reduced potency compared with FAM237A in activating GPR83, and comparison of their sequences revealed an unpaired cysteine at position 52 that is not conserved in FAM237A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 65 ] suggested that the MC4R is one of the few known GPCRs [ 66 , 67 ] where the N-terminus has a fundamental impact on signaling regulation by acting as an intramolecular (tethered/bound) ligand. The general mechanism of a tethered ligand is suspected not only for the MC4R but also for GPR83 [ 68 ], glycoprotein hormone receptors (GPHRs) [ 69 , 70 , 71 ], S1P2R [ 72 ], LGR7 [ 73 ], α 1D -adrenoceptor [ 74 ], adhesion GPCRs (aGPCR) [ 75 ], or protease-activated receptors (PARs) [ 76 ]. Tethered ligands can permanently activate the receptor to a certain degree compared to full ligand-stimulated activity, as suggested for the MC4R, or they can be silent in the basal state and be activated by enzymatic clipping, as shown for the PARs [ 76 ].…”
Section: Specific Features In the Mc4r Sequence And Structure Linkmentioning
confidence: 99%
“…The important role of melanocortin‐4 receptors (MC 4 R) in energy homeostasis, sexual functions, neuroprotection, and neurogenesis (Wikberg and Mutulis, ; Tao, ) has made these G protein‐coupled receptors attractive drug targets in the central nervous system (CNS). Despite being very promising targets for several clinical trials, there is only a limited number of therapeutically approved drugs for MC 4 Rs (Ericson et al, ), mainly because the signal transduction of MC 4 Rs is subject to considerable complexity including conformational adjustments, oligomerization, and effects of different modulators (Biebermann et al, ; Kopanchuk et al, ; Müller, Berkmann, Scheerer, Biebermann, and Kleinau, ). There is increasing evidence that MC 4 R can form homo‐ and heterodimers or higher‐order oligomers (Elsner et al, ; Kopanchuk et al, ; Nickolls and Maki, ; Rediger et al, ; Chapman and Findlay, ) and the ligand binding within MC 4 R homodimers is governed by asymmetric regulation of co‐operative‐binding sites (Kopanchuk et al, , ).…”
Section: Introductionmentioning
confidence: 99%